Allelopathic Effect of Ixora coccinea Linn. on Seed Germination and Early Seedling Growth of Paddy (Oryza sativa L.) - Neelamegam*, R. (Journal of Phytology, 2011)
Experiments were conducted to evaluate the allelopathic potential of Ixora coccinea aqueous (leaf, flower and leaf-flower) extracts on paddy (Oryza sativa L.) var. ambai-16 seed germination and seedling growth under in vitro condition. The results indicated that the leaf extract of Ixora showed more negative allelopathic (stimulatory) effect on seed germination, seedling growth, biomass production, seedling vigour index and tolerance index of paddy at low concentration as compared to control, while the higher concentrations of leaf extract and all concentrations of flower and leaf-flower extracts showed positive allelopathic (inhibitory) effect on seed germination and seedling growth parameters of paddy recorded.